(untitled) (Economics and region, 2021)
The article substantiates the expediency of state support for households implementing renewable energy projects. The experience and results of the feed-in tariff application for the solar energy development in Ukrainian households are analyzed. For comparison, the effectiveness of the solar energy deployment in the residential sector of Latvia, which has a similar potential of the industry and uses net metering as an economic incentive, is estimated. It was found that the use of high feed-in tariffs in Ukraine has provided a rapid increase in household solar energy facilities. In 2016-2020, the green electricity generation by photovoltaic solar power plants in the residential sector increased 244.3 times. At the same time, the net metering system does not have a significant impact on solar energy advancement in Latvian households. In 2019, the share of electricity from solar energy in the total electricity mix of the Baltic country was less than 0.05% and less than 0.1% among other green energy sources. Net metering in Latvia provides for the possibility of selling household green energy surpluses to the local grid at a much lower price than the average price of electricity for the population. It increases the payback period of small photovoltaic solar power plants up to 20 years and more, discouraging households from investing in renewable energy. Despite the impressive growth of small green energy capacities, the generous feed-in tariffs in Ukraine have created an excessive financial burden on the state budget, exacerbated the problems of balancing national energy system and increasing the power grid capacity, sharpened disparities in the development of various types of renewable energy sources. Instead, the Latvian net metering system, without providing a significant increase in household solar energy capacity, avoided the problems typical for Ukraine. Based on the SWOT analysis of the two national economic instrument sets for solar energy deployment, the article develops recommendations for adjusting the state support mechanisms for the effective advancement of small solar energy facilities in the housing sector of both countries.